Tensile force promotes osteogenic differentiation via ephrinB2-EphB4 signaling pathway in orthodontic tooth movement - Hang Yu; Xiaoxi Wei; Huan Jiang; Huichuan Qi; Yi Zhang; Min Hu (BMC Oral Health)
Abstract Objective To investigating whether osteogenic differentiation of osteoblasts promoted by tension force (TF) is mediated by ephrinB2-EphB4 signaling. Methods TF was applied to MC3T3-E1 cells, then CCK-8 and live/dead staining were used to detect cell proliferation. Levels of osteogenic differentiation-related factors were detected by ALP staining, ARS staining, qPCR and western blot. NVP-BHG712 was used to block EphB4 receptor. Establishing a rat orthodontic tooth movement (OTM) model, ephrinB2-Fc and NVP-BHG712 were used to treat rats. Micro-CT and H&E staining were used to detect alveolar bone. Changes of MAPK pathways were detected to investigate whether they were downstream of ephrinB2-EphB4 signaling in mediating TF promote osteogenic differentiation. Result We explored the effect of TF on MC3T3-E1 cells, and found that TF significantly promoted osteogenic differentiation, but when EphB4 receptor was blocked, the promotion was inhibited. In vivo, we found that TF improved alveolar bone formation through ephrinB2-EphB4 signaling. Further investigation into the signaling pathways revealed that TF significantly increased levels of MAPK pathways, however, when EphB4 receptor was blocked, only the promotion of p-ERK1/2 was decreased. Conclusion TF promotes osteogenic differentiation through ephrinB2-EphB4 signaling and ERK1/2 pathway is a downstream of ephrinB2-EphB4 signaling partially mediate mediates TF-induced promotion of osteogenic differentiation.